The Influence of Archives Management on the Quality of Elementary School Services in Entikong Village - Vikram Yuda Octa Firandhi; Dendi Tri Suarno; Dayang Nurhamita (Pusdikra-Publishing.com, 2024)
This research is motivated by the increasingly advanced technological era where there is more and more use of technology in terms of archiving, this has an impact on the lack of use of physical archives, based on this the researcher aims to describe the influence of archives management on service quality at elementary school especially on entikong village. This research uses a quantitative approach with the type of research used in this research is causal associative research. The sampling technique is a saturated sample, namely a sample size of 30 respondents. Data collection techniques use questionnaires and test the validity of the data using validity tests and reliability tests. The analysis prerequisite tests use the normality test, multicollinearity test and heteroscedasticity test. Hypothesis testing uses a simple regression test, namely the t test and multiple linear regression testing using the F test. The results of this research show that there is a significant influence between archiving administration on service quality with tcount>ttable with a determinant coefficient of 0.374. So it can be concluded that archives administration has a 37.4% influence on service quality, so overall it can be concluded that archives management has a significant influence on service quality at elementary school. With this research, it is hoped that all levels of teacher personnel and school principals can implement better archiving management in order to improve service quality.